Reflektierte algorithmische Textanalyse. Interdisziplinäre(s) Arbeiten in der CRETA-Werkstatt - Reiter, Nils; Pichler, Axel; Kuhn, Jonas (De Gruyter, 2020)
The Center for Reflected Text Analytics (CRETA) develops interdisciplinary mixed methods for text analytics in the research fields of the digital humanities. This volume is a collection of text analyses from specialty fields including literary studies, linguistics, the social sciences, and philosophy. It thus offers an overview of the methodology of the reflected algorithmic analysis of literary and non-literary texts.